2015
DOI: 10.1002/macp.201500148
|View full text |Cite
|
Sign up to set email alerts
|

Successive Synthesis of Multiarmed and Multicomponent Star‐Branched Polymers by New Iterative Methodology Based on Linking Reaction between Block Copolymer In‐Chain Anion and α‐Phenylacrylate‐Functionalized Polymer

Abstract: A series of multiarmed and multicomponent miktoarm (μ‐) star polymers have been successfully synthesized by developing a new iterative methodology based on a specially designed linking reaction of the block copolymer in‐chain anions, whose anions are positioned between the blocks, with α‐phenylacrylate (PA)‐functionalized polymers. The iterative methodology involves the following two reaction steps: a) introduction of two different polymer segments by the linking reaction of a block copolymer in‐chain anion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Multiarm star polymers containing linear polymeric chains emanating as “arms” from a central branching point, or core, represent one of the simplest branched topologies with spherical shape, high functionality, low viscosity, and dense structure and provide properties and functions as compared to their linear analogs with similar molecular weight . Until recently, the living ionic polymerization procedures mostly anionic polymerization were the only system for the preparation of the multiarm star polymers . Without a doubt, the introduction of living radical polymerization (LRP) routes has enabled the synthesis of multiarm star polymers with a cross‐linked core from a wide range of monomers under less stringent reaction conditions with good control over dispersity .…”
Section: Introductionmentioning
confidence: 99%
“…Multiarm star polymers containing linear polymeric chains emanating as “arms” from a central branching point, or core, represent one of the simplest branched topologies with spherical shape, high functionality, low viscosity, and dense structure and provide properties and functions as compared to their linear analogs with similar molecular weight . Until recently, the living ionic polymerization procedures mostly anionic polymerization were the only system for the preparation of the multiarm star polymers . Without a doubt, the introduction of living radical polymerization (LRP) routes has enabled the synthesis of multiarm star polymers with a cross‐linked core from a wide range of monomers under less stringent reaction conditions with good control over dispersity .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, for the methodology developed in this study, all the living anionic polymers derived from the methacrylate monomers and 2-VP with less nucleophilicities are readily introduced as either the graft or the main chain by reacting each of them with the PA reaction site. Furthermore, since highly reactive living anionic PS, PI, and PB have already been reported to react with the PA reaction site based on our previous studies, these polymer segments are also used in the graft copolymer synthesis. Thus, the developed methodology becomes more general and versatile than those already reported for the synthesis of exact graft copolymers. , …”
Section: Discussionmentioning
confidence: 99%
“…All the materials and measurements in this study were reported in our previous papers , and described in the Supporting Information.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Very recently, a new and improved methodology has been proposed, as illustrated in Scheme 2 [ 49 , 50 , 51 , 52 ]. The key of this methodology is to utilize two functionalities, X 1 and X 2 , which can be deprotected in turn to separately convert to the first and second Y reaction sites.…”
Section: Macromolecular Architecture Syntheses By Iterative Methodmentioning
confidence: 99%